Sputtered PbI2 with Post‐Processing for Perovskite Solar Cells - Hwang, Jae-Keun; Lee, Sang-Won; Lee, Wonkyu; Bae, Soohyun; Kang, Dongkyun; Jeong, Seok-Hyun; Lee, Solhee; Pyun, Dowon; Hwang, Ji-Seong; Cho, Sujin; Kim, Donghwan; Kang, Yoonmook; et al. (Solar RRL, 2023)
Conformal deposition of perovskite films on textured silicon surfaces using a dry process is crucial for producing high‐performance perovskite/silicon tandem solar cells. Herein, a radio frequency magnetron sputtering process is used with a PbI2 target to deposit precursor films. Iodination, thermal annealing, and dimethyl sulfoxide treatment are employed as posttreatment processes to improve the stoichiometry, crystallinity, and surface morphology of the PbI2 precursor. The precursor films are converted into perovskite using direct contact conversion process, and the interfacial and bulk properties are enhanced by methylamine vapor annealing to fabricate perovskite solar cells with a power conversion efficiency of 12.2%. Also, 18.3% efficiency is confirmed at a wider voltage sweep range, which suggests that further efficiency improvement is possible by removing defects inside the perovskite. Finally, uniform perovskite films are conformally deposited on a 25 cm2 textured silicon surface. With such high‐efficiency potential and conformality, the method of sputtering PbI2 can open a new way to fabricate perovskite/silicon tandem solar cells. PbI2 precursor films are deposited using a sputtering process and treated with iodination, thermal annealing, and dimethyl sulfoxide to improve their properties. Perovskite solar cells are fabricated using direct contact conversion and methylamine vapor annealing, achieving 12.2% efficiency with potential for further improvement. Uniform perovskite films are deposited on large‐area textured silicon, enabling application in perovskite/silicon tandem solar cells.